Health status of cows fed maize silage covered with oxo-biodegradable foil - Piotr SZTERK; Piotr DORSZEWSKI; Małgorzata GRABOWICZ; Lucyna PODKÓWKA (Journal of Central European Agriculture, 2017)
In agricultural practice, silage production uses pure, low density polyethylene foil. This foil, after use, becomes farm waste, having a negative impact on the environment. Instead of conventional foil, an environmentally safe biodegradable foil can be used, made from naturally occurring polymers or from synthetic multiparticulates, easily degradable by microorganisms. Silage covered with this type of foil should be safe for animal health. The purpose of the study was to determine whether oxo-biodegradable film could be used instead of conventional film in agricultural practice, to produce silage that is safe for the cows' health. Dairy cows were fed a partly mixed ratio (PMR), the component of which was silage made of whole maize plants, covered with oxo-biodegradable foil. The cow blood serum was marked for content of: glucose, total protein, cholesterol, triacylglycerols and enzyme activity: aspartic and alanine aminotransferase, γ-glutamyl transferase, alkaline phosphatase and amylase. The total protein concentration in the serum of cows analyzed at the end of the experiment was higher than the commonly accepted normal values. The content of glucose, cholesterol, triacylglycerols and the activity of aspartate and alanine aminotransferase, γ-glutamyl transferase, alkaline phosphatase and amylase was within reference limits. Feeding of silage from whole maize plants covered withoxo-biodegradable foil did not negatively affect the biochemical indicators of the cows' blood serum. The silage proved to be safe for the cows' health.